Peran Guru Pendidikan Agama Islam dalam Pembinaan Akhlak Siswa di MA Unggulan al-Kautsar Trowulan Mojokerto - Nurul Afifa; Mohammad Saat Ibnu Waqfin (Lembaga Yasin AlSys, 2026)
Islamic Religious Education (PAI) teachers have a strategic role in shaping students’ moral and spiritual development. However, social change, technological development, and symptoms of moral degradation among students require PAI teachers to perform broader roles than merely delivering learning material. This study aims to analyze the role of PAI teachers in shaping students’ morals and character in educational environments. This study used a qualitative approach with a library research design. Data were obtained from books, scientific journals, and academic publications relevant to Islamic education, character education, and moral development, then analyzed using content analysis techniques. The results showed that PAI teachers played a role in shaping students’ morals through their functions as educators, role models, mentors, counselors, and facilitators of religious activities. Moral formation was carried out through the habituation of positive behavior, the implementation of religious activities, and the creation of a religious school culture. In addition, collaboration among teachers, parents, and the community also strengthened the effectiveness of character education. The conclusion of this study affirms that the success of students’ moral formation depends not only on the delivery of religious knowledge but also on the exemplary conduct and active involvement of PAI teachers in students’ daily lives. These findings imply the importance of educational institutions’ support for comprehensive character education programs to shape a generation with noble character and a strong spiritual foundation.